2009
DOI: 10.1016/j.biopsych.2008.10.040
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Cystine-Glutamate Exchange in Nicotine Dependence in Rats and Humans

Abstract: Background The present study determined if, akin to cocaine, nicotine self-administration in rats induces adaptations in the expression of glutamate transporters and cystine-glutamate exchangers in brain nuclei implicated in reinforcement, and if treating cigarette smokers with a drug that restores cystine-glutamate exchange affected the number of cigarettes smoked. Methods Rats self-administered nicotine intravenously for 12 hours/day or received nicotine through osmotic mini-pumps for 21 days. Somatic sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
281
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 240 publications
(300 citation statements)
references
References 21 publications
19
281
0
Order By: Relevance
“…In addition, astrocytes are able to exchange glutamate for cystine (cyteine disulfide) through the cystine-glutamate exchanger, system Xc-, which allows cystine to be used for astrocytic GSH synthesis (O 'Connor et al, 1995). Cystineglutamate exchange (Xc-) is downregulated by daily cocaine or nicotine administration, and the ensuing decrease in release of non-synaptic glutamate via system Xc-contributes to relapse vulnerability in animal models of addiction (Baker et al, 2003;Knackstedt et al, 2009;Madayag et al, 2007). Although research has focused on system Xc-mediated release of glutamate, it is possible that by downregulating system Xc-daily cocaine may also affect cellular redox via decreasing substrate for de novo GSH synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, astrocytes are able to exchange glutamate for cystine (cyteine disulfide) through the cystine-glutamate exchanger, system Xc-, which allows cystine to be used for astrocytic GSH synthesis (O 'Connor et al, 1995). Cystineglutamate exchange (Xc-) is downregulated by daily cocaine or nicotine administration, and the ensuing decrease in release of non-synaptic glutamate via system Xc-contributes to relapse vulnerability in animal models of addiction (Baker et al, 2003;Knackstedt et al, 2009;Madayag et al, 2007). Although research has focused on system Xc-mediated release of glutamate, it is possible that by downregulating system Xc-daily cocaine may also affect cellular redox via decreasing substrate for de novo GSH synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, inhibition of system xc-prevented the NAC-induced recovery of extracellular glutamate levels in this region, implicating the xc-system in the neurobiological mechanisms whereby NAC normalises cocaine-induced extracellular glutamate dysregulation (Baker et al, 2003a). Thus, NAC may induce a recovery of the downregulated xCT and GLT-1 function (Knackstedt et al, 2009;2010a). Indeed, the recovery of an altered GLT-1 function allows for increased transport of glutamate into the astrocyte while the recovery of altered system xcfunction by xCT recovery allows for increased export of glutamate back into the extrasynaptic space (see Figure 1).…”
Section: Mechanisms Of N-acetylcysteine Actionmentioning
confidence: 86%
“…In addition to protecting brain cells from the oxidative stress, GSH has been shown to enhance responsivity of NMDA receptors to glutamatergic stimulation (see Janáky et al, 1999), suggesting some direct modulation of glutamatergic signalling as a result of NAC administration. The role of GSH in addiction has yet to be determined, and thus far, the effects of NAC as a pharmacotherapy for drug dependence appear to be primarily mediated via its actions on system xc-and GLT-1 (Knackstedt et al, 2009;Knackstedt et al, 2010a). 3. N-acetylcysteine in animal models of self-administration, reinstatement, and relapse…”
Section: Mechanisms Of N-acetylcysteine Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the novel dopamine D3 receptor antagonist GSK598809, currently being tested as a treatment for nicotine addiction, was shown to attenuate the rewarding and motivational effects of nicotine in rodents [20][21][22][23][24][25]. In an exciting recent study, Kalivas and colleagues demonstrated that N-acetylcysteine -a drug that promotes cystine-glutamate exchange -decreases signs of withdrawal in nicotine-dependent rats and reduces the number of cigarettes smoked by tobacco-dependent humans [26]. The drugs d-cycloserine (NMDA receptor partial agonist) and GW468816 (glycine-site NMDA receptor antagonist), also targeting glutamatergic transmission, are also being tested in human smokers for efficacy in facilitating smoking cessation and to reduce rates of relapse, respectively.…”
Section: Editorialmentioning
confidence: 99%